Prevalence and Characteristics of Erectile Dysfunction in Obstructive Sleep Apnea Patients - Feng, Chen; Yang, Yan; Chen, Lixiao; Guo, Ruixiang; Liu, Huayang; Li, Chaojie; Wang, Yan; Dong, Pin; Li, Yanzhong (Frontiers in Endocrinology, 2022)
Background Obstructive sleep apnea (OSA) is a common and severe social problem. Erectile dysfunction (ED) is an important health concern. The incidence of OSA with ED is increasing, which significantly affects the quality of life and work efficiency of patients. However, the mechanism underlying the comorbidity of these two diseases remains unclear. Objectives (1) Investigate the incidence of OSA with ED; (2) analyze the correlation between OSA and ED; and (3) explore the treatment response to and possible mechanism of uvulapalatopharyngoplasty (UPPP) in patients with OSA and ED. This study aims to provide a theoretical basis for the clinical diagnosis and comprehensive treatment of OSA with ED and improve prevention and treatment strategies. Materials and Methods In total, 135 subjects were enrolled in the study. Clinical data, polysomnography, the ESS score, Beck anxiety score, Beck depression score, IIEF-5 score and ASEX score were recorded before UPPP and 6 months after UPPP. Sex hormones were measured for all subjects using a Roche electrochemiluminescence analyzer. Result The incidence of OSA with ED was 64.52%, and the incidence of severe OSA with ED was 73.02%. The incidence of OSA with ED increased with age, BMI and apnea-hypopnea index (AHI) value. Among polysomnography indicators, minimum oxygen saturation and average oxygen saturation may predict the occurrence of OSA with ED. Improving the patient's anxiety and depression is very important for treating OSA with ED. Sex hormone levels were not significantly correlated with the occurrence of OSA with ED. Conclusion ED is a common symptom of OSA patients. This study showed that sex hormone levels in OSA patients with ED were not significantly correlated with the condition, but further investigation of this relationship is worthwhile. It is recommended that the free and combined types of sex hormones be further distinguished during testing because the free type is the active form. UPPP surgical treatment is effective for OSA with ED, and its possible mechanism is protection of the peripheral nerves of the sex organs by improving nighttime hypoxia and arousal.